2014
DOI: 10.1016/j.jspr.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Effective and economic storage of pigeonpea seed in triple layer plastic bags

Abstract: Pigeonpea [Cajanus cajan (L.) Millsp.] seed stored in triple layer Purdue Improved Cowpea Storage (PICS) bags for eight months retained germination and seed integrity significantly better than seed stored in traditional gunny bags. PICS bags prevented major damage caused by bruchids (Callosobruchus maculatus F.), while grain stored in gunny bags suffered severe losses. The aflatoxin levels in stored seed were low and not significantly different between the two storage systems. The levels of O 2 in PICS bags ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 16 publications
9
29
0
Order By: Relevance
“…This was not the case for maize stored in woven bags, especially those infested by the weevil. These results are consistent with the results of other studies focused on PICS bags, which demonstrated better outcomes for grain stored in the triple bags than for grain stored in other ways [10, 11, 1621]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was not the case for maize stored in woven bags, especially those infested by the weevil. These results are consistent with the results of other studies focused on PICS bags, which demonstrated better outcomes for grain stored in the triple bags than for grain stored in other ways [10, 11, 1621]. …”
Section: Discussionsupporting
confidence: 92%
“…PICS bags had higher internal R.H. and maintained grain moisture better than woven bags, in which the grain dried out as ambient R.H. dropped over the 8 month storage period. This is consistent with previous observations showing the PICS bags have a more stable R.H. environment than other bag types [7, 21]. A stable moisture environment is beneficial from a farmer’s perspective, as it creates an expectation that initial grain moisture conditions will remain the same so long as the bag is closed.…”
Section: Discussionsupporting
confidence: 91%
“…Control of bruchid reproduction and damage by triple layer (PICS) bags has been reported in several crops in the recent past (Vales et al, 2014;Baoua et al, 2012;Murdock et al, 2012). In our present study, pod damage by bruchids was less in triple layer bags compared to cloth bags under all conditions (Figs.…”
Section: Discussionsupporting
confidence: 57%
“…Cloth bags were selected since they work on the same principle as that of jute/ gunny bags in permitting air exchange with the surrounding environment. Triple-layer bags were carefully inspected for holes and sealing imperfections, to ensure that only good quality bags were used (Vales et al, 2014).…”
Section: Storage Bags and Descriptionmentioning
confidence: 99%
“…Originally developed to reduce insects damage to stored cowpeas in western and central Africa (Murdock et al., 2012), the bags have been evaluated for other commodities such as maize, groundnut, and pigeon pea (Baoua et al., 2014, Murdock et al., 2012, Sudini et al., 2015, Vales et al., 2014, Williams et al., 2014). Biological activity within the bags, including respiration from the stored products and/or the insects and grain, decreases oxygen and increases carbon dioxide to levels that are insecticidal.…”
Section: Introductionmentioning
confidence: 99%